Tinjauan Terhadap Keberadaan Bahan Pustaka di Rak dan di dalam Database Digilib Perpustakaan Universitas Negeri Padang - Marliani, yani; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purposes of this study were to explain the fit of retrieved information in Digilib the library application program with library material on rack at the library of Padang State University; and to find out the caused factors of the difference between the library material on rack and information in Digilib at the library of Padang State University. Interviewing and observation technique were used and observation in data gatheting. By using interview and observation result description in the data was analyzed. The results of this study are: (1) the information in Digilib was not appropriate with material library at rack and so the students felt a disappointed (2) caused factors of the difference between the library material on rack and information in Digilib at the library of Padang State University are: errors in data entry, unexistence of stock opname and wrong placing of library material on the rack. Keywords: library, information, Digilib, library material